EFEKTIVITAS PEMBERIAN BEBERAPA JENIS PUPUK ORGANIK TERHDAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Muhammad Irvani Habibie; Akhmad Rizali; Antar Sofyan (Agroekotek View, 2019)
Shallot is a horticulture plant that is best known to the public because it has a very important meaning in life, one of which is as a kitchen spice or a complete spice. One effort that can be done to increase shallot production is by cultivating shallots varieties that are in accordance with climatic and soil conditions and by applying organic fertilizers in order to reduce the high price of shallots in the market. Organic fertilizers are developed in order to create quality fertilizers that are able to restore land productivity and can reduce the application of chemical or synthetic fertilizers. The purposeeof this study wasnto determine the effectiveness of giving several types of organicnfertilizers to the growthnandnyield of shallots (Allium ascalonicum L.). This research was conducted using one factor randomized block design (RBD), which consisted of 4 treatment levels, namely P1: control; P2: organic fertilizer based on chicken manure 2 kg / plot; P3: organic fertilizer made from cow dung 2 kg / plot; and P4: organic fertilizer made from water hyacinth 2 kg / plot. The results of this study indicate that there is effectiveness in the treatment by providing several types of organic fertilizers made from chicken manure (P2), cow manure (P3), and water hyacinth (P4) which have a significant effect on plant height, leaf number, and wet weight tuber on red onion plants, and the results obtained that fertilizer made from chicken manure are better organic fertilizers to increase the growthnandnproduction of shallots.